2005
DOI: 10.1007/s00540-005-0336-y
|View full text |Cite
|
Sign up to set email alerts
|

Drugs to facilitate recovery of neuromuscular blockade and muscle strength

Abstract: Several drugs that quicken recovery from neuromuscular blockade caused by vecuronium in anesthetized patients are reviewed. Ulinastatin, a protease inhibitor, is thought to promote the release of acetylcholine at the neuromuscular junction and increases hepatic blood flow and urine volume. For this reason, ulinastatin quickens recovery from neuromuscular blockade in anesthetized patients receiving vecuronium. Additionally, pretreatment with ulinastatin avoids prolongation of vecuronium-induced neuromuscular bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Nicorandil enhances membrane K+ conductance in skeletal muscle and increases contraction of the skeletal muscle and quickens recovery from neuromuscular blockade. [3]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicorandil enhances membrane K+ conductance in skeletal muscle and increases contraction of the skeletal muscle and quickens recovery from neuromuscular blockade. [3]…”
Section: Discussionmentioning
confidence: 99%
“…[8] in their study found that infusion of amino acids @ 100ml/ hour speeds the recovery from vecuronium induced neuromuscular blockade in anaesthetized patients. This could be probably explained by the fact that amino-acid–enriched solutions supply energy to the skeletal muscles, causing an increase in muscle strength and hastening recovery from neuromuscular blockade by generating heat in the skeletal muscles and thus improving the hypothermia during general anaesthesia,[3]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulators of the K ATP channels are promising in those conditions associated with impaired skeletal muscle functionality. Openers restore muscle contraction in humans affected by periodic paralysis, myotonia, and in neuromuscular disorders associated with impaired fiber excitability and contraction; deficiency of skeletal muscle K ATP channels is associated with reduced muscle contractility in the rat (Saitoh, 2005;Cifelli et al, 2007). Blockers targeting the Kir6.2 subunit may be effective in the insulin-resistant state and diabetes type II with neuromuscular symptoms associated with abnormal openings of the skeletal muscle, neuronal, and pancreatic K ATP channels (Koster et al, 2005;Flechtner et al, 2006).…”
Section: Potassium Channel Modulators and Skeletal Muscle 57mentioning
confidence: 99%
“…contractility function in humans after neuromuscular blocker-induced paralysis (Saitoh, 2005). Pinacidil is capable of reducing the severity and frequency of paralysis in patients affected by hypokalemic periodic paralyses (hypoPP); however, the patients suffer severe hypotension, which limits its use in this muscle disorder (Links et al, 1992).…”
mentioning
confidence: 99%